Childhood socioeconomic factors and perinatal characteristics influence development of rheumatoid arthritis in adulthood. Issue 3 (14th May 2012) - Parks, Christine G; D'Aloisio, Aimee A; DeRoo, Lisa A; Huiber, Kirstin; Rider, Lisa G; Miller, Frederick W; Sandler, Dale P
Abstract : Background: Rheumatoid arthritis (RA) has been associated with lower socioeconomic status (SES), but the reasons for this are not known. Objectives: To examine childhood SES measures, SES trajectory and other perinatal factors in relation to RA. Methods: The sample included 50 884 women, aged 35–74 (84% non-Hispanic white) enrolled 2004–9 in a US national cohort study. In baseline questionnaires, cases (N=424, 0.8%) reported RA diagnosis after age 16, ever use of disease-modifying antirheumatic drugs or steroids for RA and ≥6 weeks bilateral joint swelling. Childhood SES measures are presented as OR and 95% CI adjusted for age and race/ethnicity. Analyses of perinatal factors also adjusted for childhood SES, and joint effects of childhood and adult SES and smoking exposures were evaluated. Results: Patients with RA reported lower childhood household education (<12 years vs college degree; OR=1.7; 95% CI 1.1 to 2.5), food insecurity (OR=1.5, 95% CI 1.1 to 2.0) and young maternal age (<20 vs 20–34 years; OR=1.7, 95% CI 1.2 to 2.5), with a trend (p<0.0001) for increasing number of adverse factors (OR=3.0; 95% CI 1.3 to 7.0; 4 vs 0 factors) compared with non-cases. Low birth weight (<2500 g) and preconception paternal smoking were independently associated with RA. Together, lower childhood SES and adult education (<college degree) were associated with RA (interaction p=0.03), with a joint effect magnitude similar to a history of paternal and adult smoking. Conclusions: RA was associated with low childhood SES sustained into adulthood, with cumulative effects across multiple measures, suggesting the importance of other unmeasured factors linking SES and RA.